Development and evaluation of yeast-based GFP and luciferase reporter assays for chemical-induced genotoxicity and oxidative damage - Suzuki, Hajime; Sakabe, Takahiro; Hirose, Yuu; Eki, Toshihiko (Applied microbiology and biotechnology, 2017)
We aimed to develop the bioassays for genotixicity and/or oxidative damage using the recombinant yeast. A genotoxicity assay was developed using recombinant Saccharomyces cerevisiae strain BY4741 with a green fluorescent protein (GFP) reporter plasmid, driven by the DNA damage-responsive RNR3 promoter. Enhanced fluorescence induction was observed in DNA repair-deficient strains treated with methyl methanesulfonate, but not with hydrogen peroxide. A GFP reporter yeast strain driven by the oxidative stress-responsive TRX2 promoter was newly developed to assess oxidative damage, but fluorescence was poorly induced by oxidants. In place of GFP, yeast strains with luciferase gene reporter plasmids ( luc2 and luc2CP , encoding stable and unstable luciferase, respectively) were prepared. Transient induction of luciferase activity was clearly detected only in a TRX2 promoter-driven luc2CP reporter strain within 90 min of oxidant exposure. However, luciferase was strongly induced by hydroxyurea in the RNR3 promoter-driven luc2 and GFP reporter strains over 8 h after the exposure, suggesting that the RNR3 promoter is continuously upregulated by DNA damage, whereas the TRX2 promoter is transiently activated by oxidative agents. Luciferase activity levels were also increased in a TRX2 -promoter-driven luc2CP reporter strain treated with tert- butyl hydroperoxide and menadione and weakly induced with diamide and diethyl maleate. Weakly enhanced luciferase activity induction was detected in the sod1Δ , sod2Δ , and rad27Δ strains treated with hydrogen peroxide compared with that in the wild-type strain. In conclusion, tests using GFP and stable luciferase reporters are useful for genotoxicity, and oxidative damage can be clearly detected by assay with an unstable luciferase reporter.